Meningkatkan Kemandirian Anak Menggunakan Metode Bermain Peran pada Kelompok A TK PGRI Jatisela - Maryam, Siti (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2019)
[Title: Improving the Students’ Independence using Role Playing Methods in Group A TK PGRI Jatisela]. This study aims to improve the students’ independence through role-playing learning with teaching aids and tell stories in kindergarten group A in PGRI Jatisela, Sesela, Gunungsari, West Lombok. This research is a Classroom Action Research (CAR) with a qualitative approach because in this study prioritizes descriptive-analytic to solve the concepts in it, not using numerical-statistical concepts with 21 research subjects. The students’ independence observed in this study using the observation sheet were the students’ independence in wearing shoes and wearing clothes. The results showed that there was an increase in students' independence after the learning cycle. The students’ independence in wearing shoes (9.5% in cycle I) and wearing clothes (4% in cycle I) increase to 100% in cycle II. Based on the results, it can be concluded that role-playing learning with teaching aids and tell stories in group A the Jatisela PGRI Kindergarten, Sesela, Gunungsari, West Lombok can increase students’ independence in wearing shoes and wearing clothes.